Penegakan Hukum Dan Faktor Yang Mempengaruhi Terhadap Pelaku Tindak Pidana Politik Uang Dalam Pemilihan Umum - Muhammad Alfata Birza; Hanafi Amrani (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
One of the election criminal offenses that almost always occurs during general elections is money politics. Gakkumdu as an institution tasked with handling election crime cases will not remain silent. Gakkumdu has taken various preventive measures. The data released by Bawaslu shows that Gakkumdu's handling efforts have not been successful, so there are questions about Gakkumdu's performance and the problems he faces in enforcing the law on election crime violations, especially related to money politics. So how is law enforcement against perpetrators of criminal acts of money politics in general elections and what factors influence law enforcement of criminal acts of money politics in general elections The method used in this research is Empirical legal research because the subject of this research is an interview with the authorities in Bawaslu RI. The approach used is a quantitative approach using primary data, secondary data, and tertiary data. The results show that, first of all, Law No. 7 of 2017 concerning General Elections has regulated the procedures for handling criminal acts in the 2024 Elections through law enforcement of election crimes called Sentra Gakkumdu, consisting of elements of Bawaslu and or its ranks to the District Panwaslu, the Indonesian National Police and or its ranks to the Resort Police, and the Attorney General's Office of the Republic of Indonesia and or its ranks to the District Attorney's Office. However, in reality, the existence of the Gakkumdu Center does not make the law enforcement process for criminal acts in the 2024 Elections effective, because it turns out that many reports or findings of election crimes fail to be processed until examination in court due to disagreements between the three elements in the Gakkumdu Center as a result of unclear arrangements in Law No. 7 of 2017 on Elections Second, there are several reasons why Gakkumdu faces difficulties in handling violations of the criminal act of money politics. The first is the legislation factor. Second, law enforcement factors Third, community factors.